Ecosystem services or services to ecosystems? Valuing cultivation and reciprocal relationships between humans and ecosystems. (September 2015) - Comberti, C.; Thornton, T.F.; Wylliede Echeverria, V.; Patterson, T.
Graphical abstract: Highlights: The Ecosystem Services concept of a one-way flow of services to people is too simple. Human-ecosystem relations are reciprocal, as evidenced by Indigenous peoples and their environments. The concept of 'Services to Ecosystems' (S2E) is developed and a modified framework proposed. Services to Ecosystems are illustrated using case-studies from Amazonia and the Pacific Northwest. Management applications and practical improvements using the Services to Ecosystems concept are discussed. Abstract: The concept of Ecosystem Services (ES), widely understood as the "benefits that humans receive from the natural functioning of healthy ecosystems" (Jeffers et al., 2015 ), depicts a one-way flow of services from ecosystems to people. We argue that this conceptualisation is overly simplistic and largely inaccurate, neglecting the reality that humans often contribute to the maintenance and enhancement of ecosystems, as often evidenced (but not exclusively) in many traditional and Indigenous societies. Management interventions arising from Ecosystem Services research are thus potentially damaging to both ecosystems and indigenous rights. We present the concept of 'Services to Ecosystems' (S2E) to address this, closing the loop of the reciprocal relationship between humans and ecosystems. Case studies from the biocultural ecosystems of Amazonia and the Pacific Northwest of North America (Cascadia) are used to illustrate the concept and provide examples of Services to Ecosystems in past and current societies. Finally, an alternative framework is presented, advancing the existing framework for Ecosystem Services by incorporating this reconceptualization and the loop of reciprocity. The framework aims to facilitate the inclusion of Services to Ecosystems in management strategies based upon Ecosystem Services, and highlights the need for ethnographic research in Ecosystem Service-based interventions.